ANALISIS MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA MATA PELAJARAN PKN KELAS IV DI MADRASAH IBTIDAIYAH DARUL DA'WAH WAL IRSYAD SEPPANGE DESA TUNGKE KECAMATAN BENGO KABUPATEN BONE - Nur Azizah Fitratul Awaliah; Andi Tabrani Rasyid; Hasanuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by students' low understanding of Civics Education (PKn), resulting from teacher-centered instruction. Based on John Dewey's constructivist theory, learning becomes more effective when students are actively involved in solving problems. This study aims to describe the implementation of the Problem Based Learning (PBL) model in Civics Education for fourth-grade students at Madrasah Ibtidaiyah Darul Da'wah wal Irsyad Seppange, Tungke Village, Bengo Subdistrict, Bone Regency. A descriptive qualitative approach was used, involving the fourth-grade teacher and 19 students as research subjects. Data were collected through observation, in-depth interviews, and documentation, and were analyzed through data reduction, data display, and conclusion drawing/verification. The results show that the implementation of PBL was able to develop students' activeness, motivation, and understanding of Civics material. Students became more active in discussion, more confident in expressing ideas, and better able to reason critically in solving problems related to daily life. Although constrained by time management and differences in students' abilities, the PBL model proved effective in supporting the Civics learning process.